MOBILE STEREO-VISION OBJECT TRACKING ROBOT - ISHAK, MUNIRA NUR FARIZAN (Universiti Teknologi PETRONAS, 2007)
Building a mobile robot withsight capabilities enables the robot to do simple tasks of following a straight line or avoiding an obstacle, which in this project, a more complicated task of following an object or human. This project is carried out exploring the sight capability of the robot through computer vision, which implements image and video processing, and also the stereo-vision concept which gives depth perception to the sight ofthe robot. The primary objective is to develop a mobile robot that has the capabilities to do object tracking in real time, with stereovision, utilizing two separate cameras. The movement of the robot is programmed using Cprogramming for the microcontroller, which controls DC motors built with a gearing system onthe mobile robot. This program enables robot to move in left, right and forward directions. The objecttracking and image processing is developed using the MATLAB program. Image acquisition is done using web cameras. A reference image is saved, from which the object is tracked. Once object is tracked, MATLAB sends instructions to the microcontroller via serial communication, RS232. Different techniques of digital image processing are used such as edge detection and correlation. The project methodology stresses on the research and analysis, circuit design, circuit modeling, microcontroller programming, circuit fabrication and finally, designing the interfacing software. The end system comprises of the hardware for the mobile robot and interfacing software for object tracking.